Pengaruh Fanatisme, Packaging, Promotion, dan Product Innovation terhadap Keputusan Pembelian Produk BTS Meal Mcdonald’s di Soloraya - Yelia Nova Khoiriah; Ginanjar Rahmawan (CV. Publikasi Indonesia, 2022)
The high demand for McDonald's BTS Meal products caused a stir because all McDonald's outlets were busy being invaded by online motorcycle taxis, resulting in very dense queues during the Covid-19 pandemic, even foreign news such as South Korea and India covered this. This study aims to determine the effect of fandom, packaging, promotion, and product innovation on purchasing decisions for McDonald's BTS Meal in Solo Raya. This type of research is quantitative, sampling is done by accidental sampling method, which is to determine the sample taken according to the wishes of the researcher. The query results were analyzed using the SPS statistical procedure to determine its impact on consumer purchases through testing, reliability testing, classical estimation test, multiple regression analysis, f test, decision test, and t-test. The results of hypothesis testing indicate that fandom, packaging, promotion, and product innovation have a significant effect on consumer purchasing decisions.